Pengenalan Flora Endemik Dan Status Konservasinya Melalui Sosialisasi Di SMP Negeri 10 Langsa, Aceh - Akbar, M. Ali; Sri Jayanthi; Dian Syahputri; Suci Nurlida Sapitri; Amanda Lestari; Aini Ramadila; Fitria Almahliza; Dwi Syaravicena; Khairunnisa; Viska Annisa Sabrini; Mardiah; Cut Salsabila Meutiasari; Devi Anisa (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Indonesia is known as the center of world biodiversity. One of this diversity is endemic flora. Regular maintenance and protection or preservation of endemic flora to prevent or avoid damage and extinction can be done through conservation. The subjects of this program are grade 7 students. At this level, children tend to be able to understand and start thinking critically and logically, so it is hoped that the message given can be conveyed well. Based on the results of the socialization that had been carried out, it was found that there was an increase in knowledge about endemic and rare flora in Indonesia which must be protected and preserved, in other words the socialization carried out was successful in increasing students' knowledge. It is hoped that this increased understanding can encourage students to play a more active role in environmental conservation activities, both in the school environment and in the community. This electronic document is a “live” template. The various components of your paper [title, text, tables, figures and references] are already defined on the style sheet, as illustrated by the portions given in this document.